Development of stroke hand gripper innovation as an alternative tool for independent range of motion (ROM) in stroke patients - Susanti, Susanti; Gustini, Sri; Husaini, Muhammad; Aiyub, Aiyub (Science Midwifery, 2025)
Background: Stroke or Cerebral Vascular Accident (CVA) is a condition of rapid loss of neurological function due to impaired blood vessel perfusion. Stroke is caused by factors including: cerebral platelets, Hemorrhage, and Embolism. The impact of stroke is the occurrence of hand drop which is characterized by the inability to lift the wrist, move the fingers or experience weakness in the hand area. One of the treatment efforts to minimize the impact of stroke is to do Range of Motion (ROM) Exercises early. The purpose of this study is to develop a ROM aid as an alternative tool for independent ROM (stroke hand gripper) and assess its efficiency on the strength of the muscles of the fingers. Method: This study involved 30 respondents in the working area of ​​the Cot Seumeureung Community Health Center, West Aceh Regency, using purposive sampling. The research design is a Combined method, namely the research and development method or R&D (Research and development) and Pre-Experiment. The results of the study showed that the average value of muscle strength before ROM exercises using ROM aids was 2.00 and the average muscle strength after ROM exercises using ROM aids was 2.35 with a significance value of 0.008 (p <0.05), thus it can be concluded that there is a significant difference in muscle strength before ROM exercises and after ROM exercises using ROM aids.